A low-cost and eco-friendly Br-doped Cu7Sn3S10 thermoelectric compound with zT around unity. Issue 12 (9th March 2021) - Deng, Tingting; Qiu, Pengfei; Xing, Tong; Zhou, Zhengyang; Wei, Tian-Ran; Ren, Dudi; Xiao, Jie; Shi, Xun; Chen, Lidong
Abstract : Through doping Br in Cu7 Sn3 S10, a peak zT around unity at 750 K has been achieved, which is a record-high value in Cu–Sn–S ternary TE compounds. This study promises a new thermoelectric material for application in the middle temperature range. Abstract : Cu–Sn–S ternary compounds have attracted great attention in the thermoelectric community because they are composed of low-cost, earth-abundant, and non-toxic elements. Among them, Cu7 Sn3 S10 shows promising thermoelectric performance in the middle temperature range. In this work, through doping Br in Cu7 Sn3 S10, a peak dimensionless figure of merit ( zT ) around unity at 750 K has been achieved. Chemical composition analysis indicates that Br has a higher solubility in Cu7 Sn3 S10 than Cl. On one hand, the Br dopant introduces additional electrons and tunes the initial overhigh carrier concentration to the optimal range. On the other hand, the Br dopant creates strong strain field fluctuation to significantly suppress the lattice thermal conductivity to as low as 0.4 W m −1 K −1 at 750 K. Its synthetic effects advance the realization of high zT around unity in Br-doped Cu7 Sn3 S10 .